High performance concrete suitable for high temperature, low humidity and high temperature difference environments

By using composite raw materials such as porous silica hydrogel, expanded perlite and phase transition capsules in concrete, the problem of concrete cracking in high temperature and low humidity and high temperature difference is solved, and the problem of concrete cracking is significantly improved. Improves the durability and mechanical properties of concrete.

CN116375424BActive Publication Date: 2025-02-11SICHUAN JINGYIDA ENG INSPECTION CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310344554.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2025-02-11
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

Existing concrete is prone to cracking in high temperature and low humidity and high temperature difference environments, resulting in a reduction in durability, and the existing technology is difficult to effectively solve this problem.

Method used

Using composite raw materials including cement, porous silica hydrogel, expanded perlite, phase change capsule and calcium sulfate, the mechanical properties and crack resistance of concrete are enhanced by forming whisker structures and gel network structures, and The temperature change rate is reduced by complicating the thermal conduction path.

Benefits of technology

It significantly reduces the possibility of concrete cracking in high-temperature drying and temperature differential environments, improves the durability and mechanical properties of concrete, and can maintain good structural integrity in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004159122820000061
    Figure BDA0004159122820000061
Patent Text Reader

Abstract

The present application relates to the field of concrete technology, and specifically discloses high-performance concrete suitable for high-temperature, low-humidity, and high-temperature difference environments. The raw materials of high-performance concrete suitable for high-temperature, low-humidity, and high-temperature difference environments include: 280-360 parts of cement, 270-430 parts of silica hydrogel, 600-680 parts of coarse aggregate, 100-220 parts of expanded perlite, 300-400 parts of sand, 100-120 parts of phase change capsules, 18-26 parts of calcium sulfate, 60-120 parts of polyisophthalamide fiber, and 18-32 parts of adhesive. The concrete prepared in this application has outstanding thermal insulation capabilities, has the advantages of high-temperature drying resistance and temperature difference resistance, and can maintain the performance of concrete under high-temperature drying and large temperature difference conditions for a long time without large-scale cracking, and has good durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete technology, and more specifically, to high-performance concrete suitable for high-temperature, low-humidity, and high-temperature difference environments. Background Art

[0002] Concrete is one of the important raw materials in construction engineering. Concrete needs to have different properties in different application scenarios and environments. In a high temperature and dry environment, concrete will be more prone to high temperature cracking, and the time of cracking will be greatly advanced, resulting in reduced durability. In a high temperature difference environment, the volume of concrete will expand and shrink. When the shrinkage value is greater than the ultimate tensile value of concrete, it will destroy the structure of the concrete and cause cracking. In the relevant technical field, there are many problems with commonly used high temperature resistant and temperature difference resistant concrete. For example, concrete with only cement as an adhesive has general adhesion and insufficient durability. The mechanical properties of the thermal insulation materials used in the raw materials of concrete are general. They are easy to break and fall off in a dry environment with a large temperature difference for a long time. For concrete cracking, there are also many patents that use fiber structures such as polypropylene fibers to improve the tensile strength of concrete, but most fibers themselves have insufficient temperature resistance and the effect is still limited. Therefore, it is necessary to develop concrete that is not prone to temperature change cracking, maintains good mechanical properties, and has good durability under long-term high temperature drying and large temperature difference conditions. Summary of the invention

[0003] In order to solve the problem that concrete is prone to cracking and reduced durability in high-temperature and dry areas with large temperature differences between day and night, this application provides high-performance concrete suitable for high-temperature and low-humidity and high-temperature difference environments.

[0004] The high performance concrete provided in this application, which is suitable for high temperature, low humidity and high temperature difference environment, adopts the following technical solutions:

[0005] High-performance concrete suitable for high-temperature, low-humidity and high-temperature-difference environments, the raw materials include, by weight: 280-360 parts of cement, 270-430 parts of silica hydrogel, 600-680 parts of coarse aggregate, 100-220 parts of expanded perlite, 300-400 parts of sand, 100-120 parts of phase change capsules, 18-26 parts of calcium sulfate, 60-120 parts of polyisophthalamide fiber, and 18-32 parts of adhesive.

[0006] By adopting the above technical scheme, calcium sulfate can form a whisker structure in concrete, which not only has good thermal insulation, heat insulation and fire resistance, but also the calcium sulfate whisker structure is compounded with porous silica and expanded perlite, which can enhance the interaction force of the filler inside the concrete, thereby improving the mechanical properties of the concrete, so that the concrete can maintain good crack resistance under conditions of large temperature difference. The porous silica in the silica hydrogel can complicate the heat conduction path, reduce the heat transfer efficiency, and significantly reduce the degree of change between the concrete temperature and the ambient temperature. It works simultaneously with the large phase change capsules filled with phase change materials to reduce the temperature change rate inside the concrete, maintain the stability of the temperature inside the concrete, and greatly reduce the damage to the concrete caused by the harsh external environment.

[0007] Preferably, the silica hydrogel is a semi-solid hydrogel formed by adding silica aerogel, silk fibroin and xanthan gum into water and mixing them evenly.

[0008] By adopting the above technical solution, silk fibroin is added to the hydrogel to construct a gel network structure with silica aerogel, thereby increasing the interaction force between the substances in the hydrogel system. Silk fibroin and xanthan gum are highly hydrophilic and can absorb a large amount of water, thereby slowing down the rate of water loss in concrete and avoiding cracking that leads to a decrease in the mechanical properties of concrete.

[0009] Preferably, the outer layer of the phase change capsule is a hard capsule layer, and the interior is filled with a phase change material.

[0010] By adopting the above technical solution, the phase change material is wrapped with a solidified resin. While the thermal insulation and heat storage capacity of the phase change material is exerted, the phase change capsule maintains a certain hardness and mechanical properties, thereby improving the high temperature resistance and temperature difference resistance of the concrete and improving the compressive strength of the concrete.

[0011] Preferably, the outer hard capsule layer can be any one of epoxy resin and phenolic resin.

[0012] By adopting the above technical scheme, resin is selected as the raw material of the outer hard fat capsule layer, and after the resin or resin raw material and curing agent are added to form the capsule, the outer layer of the capsule has good smoothness and strength, will not be worn or cracked, and can improve the mechanical properties of concrete.

[0013] Preferably, the internal phase change material is paraffin and lithium acetate dihydrate added in a weight ratio of 1:(1-3).

[0014] By adopting the above technical solution and using two phase change materials with different phase change points, effective thermal insulation can be maintained even when the temperature difference is large, thereby expanding the applicable temperature difference range of the phase change capsule and improving the temperature difference resistance of concrete.

[0015] Preferably, the preparation method of the phase change capsules comprises the following steps: first, mixing and heating two phase change materials, paraffin and lithium acetate dihydrate, until they are uniform, then slowly adding resin and resin curing agent to the phase change material while continuously stirring, and after a sufficient number of capsules are formed, taking out the prepared capsules, washing them, and finally drying them.

[0016] Preferably, the expanded perlite needs to be treated with an adhesive and adhered to the poly(m-phenylene isophthalamide) fiber segment.

[0017] By adopting the above technical solution, on the one hand, the expanded perlite is prevented from breaking and dispersing and losing the thermal insulation effect, and on the other hand, the fiber interaction with the concrete system can enhance the tensile strength and crack resistance of the concrete.

[0018] In summary, this application has the following beneficial effects:

[0019] 1. In this application, phase change capsules and hydrogel systems are used to perform temperature change protection on concrete under high-temperature drying conditions or temperature sudden change conditions. The hydrogel is hydrophilic and has strong water storage capacity. The rate of water loss during the hydration process of the concrete is controlled to avoid cracking inside the concrete due to excessive drying, thereby reducing the possibility of cracking of the concrete. At the same time, the synergistic effect of the porous structure of silica and the expansion pearls is achieved to complicate the heat transfer path and slow down the rate of temperature change of the concrete, thereby greatly reducing the occurrence of concrete cracking and improving the durability of the concrete.

[0020] 2. In the present application, silk fibroin is added to a semi-solid silica hydrogel. The silk fibroin forms a strong force network structure to stabilize the gel system. After adding it to concrete, the early strength of the concrete is improved, and the later crack resistance is improved. The expanded perlite treated with high-temperature resistant fibers is added to the concrete system to enhance the tensile strength and crack resistance of the concrete, improve the concrete's ability to withstand high-temperature drying, and improve its durability. DETAILED DESCRIPTION

[0021] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0022] In the following preparation examples and embodiments,

[0023] The cement used is P.C42.5R Portland cement;

[0024] The phenolic resin curing agent is hexamethylenetetramine;

[0025] The adhesive used is SXBOND ME300 series two-component solvent-free epoxy resin adhesive produced by Shanghai Shouxing;

[0026] The sand used is grade II sand with fineness modulus of 2.6 and mud content of 1.0%.

[0027] Preparation Example

[0028] Preparation Example 1

[0029] First, 50 kg of paraffin wax and 50 kg of lithium acetate dihydrate, two phase change materials, are mixed and heated to a uniform molten state. Then, phenol and formaldehyde resin raw materials are slowly added dropwise into the uniform phase change material, and a phenolic resin curing agent is added dropwise. The stirring speed is continuously 300 rpm / min. After 30 minutes, the required number of capsules are formed. The capsules prepared above are taken out, washed, and finally dried.

[0030] Preparation Example 2

[0031] First, 40 kg of paraffin wax and 80 kg of lithium acetate dihydrate are mixed, heated to a uniform molten state, and then phenol and formaldehyde resin raw materials are slowly added dropwise into the uniform phase change material, and a resin curing agent is added dropwise, and stirring is continued at a speed of 300 rpm / min. After 30 minutes, the required number of capsules are formed, and the capsules prepared above are taken out, washed, and finally dried.

[0032] Preparation Example 3

[0033] First, 40 kg of paraffin wax and 120 kg of lithium acetate dihydrate are mixed, heated to a uniform molten state, and then phenol and formaldehyde resin raw materials are slowly added dropwise to the uniform phase change material, and a resin curing agent is added dropwise, and the stirring speed is continuously 300 rpm / min. After 30 minutes, the required number of capsules are formed, and the capsules prepared above are taken out, washed, and finally dried.

[0034] Preparation Example 4

[0035] First, heat lithium acetate dihydrate until it is melted, then slowly drop phenol and formaldehyde as raw materials of phenolic resin and phenolic resin curing agent into the uniformly melted paraffin phase change material, and continuously stir at the same time. After 30 minutes, the required number of capsules are formed, and the prepared capsules are taken out, washed, and finally dried.

[0036] Preparation Example 4

[0037] First, heat the paraffin until it is melted, then slowly drop phenol and formaldehyde as raw materials of phenolic resin and phenolic resin curing agent into the uniformly melted paraffin phase change material, and continuously stir at the same time. After 30 minutes, the required number of capsules are formed, and the prepared capsules are taken out, washed, and finally dried.

[0038] Preparation Example 5

[0039] First, lithium acetate dihydrate is heated to melt, and then phenol and formaldehyde as raw materials of phenolic resin and phenolic resin curing agent are slowly added to the uniformly melted lithium acetate dihydrate phase change material, and the stirring speed is continuously 300 rpm / min. After 30 minutes, the required number of capsules are formed, and the capsules prepared above are taken out, washed, and finally dried.

[0040] Example

[0041] Example 1

[0042] A method for preparing high-performance concrete suitable for high-temperature, low-humidity and high-temperature difference environments comprises the following steps:

[0043] First, 60kg of 5cm-length poly(m-phenylene isophthalamide) fiber, 18kg of adhesive and 220kg of expanded perlite are mixed and stirred, and the expanded perlite is subjected to fiber adhesion treatment to obtain expanded perlite with poly(m-phenylene isophthalamide) fiber adhered thereto; the above-mentioned expanded perlite with poly(m-phenylene isophthalamide) fiber adhered thereto, 280kg of cement, 270kg of silica hydrogel, 680kg of coarse aggregate, 300kg of sand, 100kg of phase change capsules and 18kg of calcium sulfate are mixed and stirred for 60 minutes until uniform, and then taken out for concrete pouring and standard curing to obtain high temperature resistant drying. Temperature difference resistant concrete;

[0044] The preparation method of the silica hydrogel is as follows: 60 kg of silica aerogel, 5 kg of silk fibroin, 25 kg of xanthan gum and 360 kg of water are stirred for 30 minutes and then stirred for 15 minutes to obtain the silica hydrogel.

[0045] Example 2

[0046] A method for preparing high-performance concrete suitable for high-temperature, low-humidity and high-temperature difference environments comprises the following steps:

[0047] First, 90 kg of poly(m-phenylene isophthalamide) fibers with a fiber length of 5 cm, 25 kg of adhesive and 160 kg of expanded perlite are mixed and stirred, and the expanded perlite is subjected to a fiber adhesion treatment to obtain expanded perlite with poly(m-phenylene isophthalamide) fibers adhered thereto; the above-mentioned expanded perlite with poly(m-phenylene isophthalamide) fibers adhered thereto, 220 kg of cement, 350 kg of silica hydrogel, 640 kg of coarse aggregate, 350 kg of sand, 110 kg of phase change capsules and 22 kg of calcium sulfate are mixed and stirred for 60 minutes until uniform, and then taken out for concrete pouring and standard curing to obtain high temperature resistant drying. Temperature difference resistant concrete;

[0048] The preparation method of the silica hydrogel is as follows: 60 kg of silica aerogel, 5 kg of silk fibroin, 25 kg of xanthan gum and 360 kg of water are stirred for 30 minutes and then stirred for 15 minutes to obtain the silica hydrogel.

[0049] Example 3

[0050] A method for preparing high-performance concrete suitable for high-temperature, low-humidity and high-temperature difference environments comprises the following steps:

[0051] First, 120kg of poly(m-phenylene isophthalamide) fiber with a fiber length of 5cm, 32kg of adhesive and 100kg of expanded perlite are mixed and stirred, and the expanded perlite is subjected to fiber adhesion treatment to obtain expanded perlite with poly(m-phenylene isophthalamide) fiber; the expanded perlite with poly(m-phenylene isophthalamide) fiber, 360kg of cement, 430kg of silica hydrogel, 600kg of coarse aggregate, 100kg of expanded perlite, 400kg of sand, 120kg of phase change capsules and 26kg of calcium sulfate are mixed and stirred for 60min until uniform, and then taken out for concrete pouring and standard curing to obtain high temperature dry resistant and temperature difference resistant concrete; wherein the preparation method of silica hydrogel is as follows: 60kg of silica aerogel, 5kg of silk fibroin, 25kg of xanthan gum and 360kg of water are stirred for 30min and mixed for 15min to obtain.

[0052] Example 4

[0053] The method of Example 1 was followed, except that no silk fibroin was added to the silica hydrogel raw material.

[0054] Example 5

[0055] The method of Example 1 was followed, except that the phase change capsules prepared in Preparation Example 1 were replaced by the phase change capsules prepared in Preparation Example 4 in equal amounts.

[0056] Example 6

[0057] The method of Example 1 was followed, except that the phase change capsules prepared in Preparation Example 1 were replaced by the phase change capsules prepared in Preparation Example 5 in equal amounts.

[0058] Comparative Example

[0059] Comparative Example 1

[0060] The method of Example 1 was followed, except that an equal amount of the silica hydrogel in the raw material was replaced by water.

[0061] Comparative Example 2

[0062] The method of Example 1 is followed, except that an equal amount of the phase change capsules in the raw material is replaced by sand.

[0063] Comparative Example 3

[0064] The process was carried out in accordance with the scheme of Example 1, except that phase change capsules and silica hydrogel were not added to the raw materials.

[0065] Comparative Example 3

[0066] The method of Example 1 was followed, except that no calcium sulfate was added to the raw materials.

[0067] Comparative Example 5

[0068] The method of Example 1 was followed, except that calcium sulfate and silica hydrogel were not added to the raw materials, and an equal amount of silica hydrogel was replaced by water.

[0069] Comparative Example 6

[0070] The method of Example 1 is followed, except that no poly(m-phenylene isophthalamide) fiber and adhesive are added to the raw materials.

[0071] Performance testing

[0072] 1. Concrete compressive strength test

[0073] 2. Test of concrete's resistance to high temperature drying and temperature difference

[0074] Detection Methods

[0075] 1. Concrete compressive strength test: The concrete mixed in each embodiment and the comparative example was made into a 100mm×100mm×100mm cubic specimen. According to KGB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the 28d compressive strength (unit: MPa) of each specimen was tested. The test results are shown in Table 1.

[0076] 2. Test of concrete resistance to high temperature drying and temperature difference: After the test block with an age of 28 days is saturated with water, the concrete mixed in each embodiment and the comparative example is made into a cubic test piece of 100mm×100mm×100mm. After 28 days in a high temperature drying environment of 60℃ and a temperature difference of 60℃, under the temperature conditions of -10℃ and 50℃, starting with an initial temperature of 50℃, the temperature is changed every 8 hours. After 28 days, the volume loss rate (unit: %) of each test piece is detected. When the volume reduction does not exceed 5%, it indicates that the resistance to high temperature drying and temperature difference is good. The test results of the concrete shrinkage resistance are shown in Table 2.

[0077] Table 1:

[0078] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 28d tensile strength / Mpa 5.62 5.88 5.76 4.73 5.09 5.17 28d compressive strength / Mpa 45.29 45.35 45.32 44.62 45.19 45.25 Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 28d tensile strength / Mpa 4.35 4.39 3.67 4.62 4.26 3.45 28d compressive strength / Mpa 39.74 39.95 35.04 41.86 36.24 37.12

[0079] Table 2:

[0080]

[0081] Combining the performance test results of Example 1 and Example 4, it can be seen that when silk fibroin is not added, the strength and water retention capacity of the silica hydrogel decrease, and when the water evaporation rate is accelerated, small cracks are easily generated inside the concrete, and the crack resistance performance is degraded. In addition, the data in the mechanical properties test of the concrete also decreases, the volume loss increases slightly in the later stage, and the durability decreases.

[0082] Combining the performance test results of Example 1, Example 5 and Example 6, it can be seen that when a single phase change material is used to prepare phase change capsules, it can also have a good concrete insulation effect and reduce the degree to which concrete is affected by environmental changes. However, the effect of phase change capsules prepared by any one phase change material is limited. The test results show that the thermal insulation effect of the combined use of two phase change materials is better, and the mass loss of concrete is smaller. The phase change capsules prepared by the two phase change materials have better crack resistance for high-performance concrete suitable for high temperature, low humidity and high temperature difference environments, and the compressive and tensile strengths are also slightly improved.

[0083] Combining the performance test results of Example 1 and Comparative Example 1, it can be seen that when the silica hydrogel is replaced with water, the evaporation rate of water is accelerated, resulting in more primary cracks inside the concrete, and the complexity of the thermal conductivity path of the concrete without a porous silica structure is reduced, and the high temperature drying and temperature difference resistance effects are poor, resulting in not only a significant increase in mass loss, but also a decrease in the compressive strength and tensile strength mechanical properties.

[0084] Combining the performance test results of Example 1 and Comparative Example 2, it can be seen that the compressive strength does not change much when phase change capsules are not added. However, due to the increased influence of harsh environmental conditions such as high temperature and large temperature difference on the concrete, the high temperature drying and temperature difference resistance are significantly reduced, resulting in cracking of concrete under high temperature drying and large temperature difference environments, and a significant increase in quality loss.

[0085] Combining the performance test results of Example 1 and Comparative Example 3, it can be seen that when silica hydrogel and phase change capsules are not added, the thermal insulation and temperature difference resistance effects cannot be very good, most of the high temperature drying resistance and temperature difference resistance capabilities are lost, the quality loss is aggravated, and the durability of the concrete is reduced.

[0086] Combining the performance test results of Example 1 and Comparative Example 4, it can be seen that when calcium sulfate is not added, a whisker structure that interacts with the porous particles inside the concrete cannot be formed, resulting in reduced mechanical properties and temperature difference resistance and increased mass loss.

[0087] From the performance test results of Example 1 and Comparative Example 5, it can be seen that when calcium sulfate and silica hydrogel are not added, a whisker structure that interacts with the porous particles inside the concrete cannot be formed, and the heat conduction path cannot be complicated, which reduces the thermal insulation capacity and high-temperature drying resistance of the concrete. The concrete is prone to cracking, resulting in increased quality loss and reduced durability.

[0088] It can be seen from the performance test results of Example 1 and Comparative Example 6 that when the expanded perlite is not treated with adhesion fibers, the expanded perlite is randomly dispersed in the concrete. When the expanded perlite is distributed with the high-temperature resistant fibers, it can not only fix its position, but also improve the tensile strength and crack resistance of the concrete, thereby reducing mass loss and improving the durability of the concrete.

[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. High performance concrete suitable for high temperature, low humidity and high temperature difference environment, characterized by: The raw materials include, by weight: 280-360 parts of cement, 270-430 parts of silica hydrogel, 600-680 parts of coarse aggregate, 100-220 parts of expanded perlite, 300-400 parts of sand, 100-120 parts of phase change capsules, 18-26 parts of calcium sulfate, 60-120 parts of polyisophthalamide fiber, and 18-32 parts of adhesive; The silica hydrogel is a semi-solid hydrogel formed by adding silica aerogel, silk fibroin and xanthan gum into water and mixing them evenly; The outer layer of the phase change capsule is a hard capsule layer, and the inner layer is filled with a phase change material; The outer hard capsule layer is any one of epoxy resin and phenolic resin; The internal phase change material is paraffin wax and lithium acetate dihydrate added in a weight ratio of 1:(1-3); The expanded perlite needs to be treated with an adhesive and adhered to the poly(m-phenylene isophthalamide) fiber segment.

2. The high performance concrete suitable for high temperature, low humidity and high temperature difference environment according to claim 1, characterized in that: The thickness of the outer hard capsule layer is greater than 0.3 mm.

3. The high performance concrete suitable for high temperature, low humidity and high temperature difference environment according to claim 1 or 2, characterized in that: The preparation method of the phase change capsule is as follows: firstly, paraffin wax and lithium acetate dihydrate are mixed, heated to be uniform, then resin and resin curing agent are slowly added dropwise into the uniform phase change material, and stirring is performed continuously at the same time, after the required number of capsules are formed, the prepared capsules are taken out, washed, and finally dried to obtain the capsules.

Citation Information

Patent Citations

  • Method for preparing fibroin-xanthan gum aquogel bracket

    CN106362208A

  • Low-phase-transition-temperature heat storage material and preparation method thereof

    CN106753259A

  • Heat-insulation brick prepared by taking silicon dioxide hydrogel as raw material and preparation method thereof

    CN109809790A

  • Concrete coarse aggregate wrapped with carbon fibers and preparation method thereof

    CN110316989A

  • Heat storage concrete and preparation method thereof

    CN113912335A